Waveguide resonances with selectable polarization in an infrared thermal emitter - Wei-Lun Huang; Hui-Hsin Hsiao; Chih-Yu Lin; Ming-Ru Tang; Si-Chen Lee (AIP Advances, 2017)
A multi-band infrared thermal emitter with polarized waveguide resonances was investigated. The device is constructed by embedding the metallic grating strips within the resonant cavity of a metal/dielectric/metal (MDM) structure. The proposed arrangement makes it possible to generate waveguide resonances with mutually orthogonal polarization, thereby providing an additional degree of freedom to vary the resonant wavelengths and polarizations in the medium infrared region. The measured reflection spectra and the finite-difference time-domain (FDTD) simulation indicated that the electric fields of the waveguide modes with two orthogonal polarizations are distributed in different regions of the cavity. Resonant wavelengths in different polarizations can be adjusted by altering the period, the metallic line width, or the position of the embedded gold strips. The ratio of the full width at half maximum (FWHM) to the peak wavelength was achieved to be smaller than 0.035. This study demonstrated a multi-band infrared thermal emission featuring a narrow bandwidth and polarization characteristics, which is quite suitable to be applied to the non-dispersive infrared (NDIR) detection system.